2019
DOI: 10.1080/08958378.2019.1621966
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity assessment of emitted materials collected during the manufacture of water pipe plastic linings

Abstract: U.S. water infrastructure is in need of widespread repair due to age-related deterioration. Currently, the cured-in-place (CIPP) procedure is the most common method for water pipe repair. This method involves the on-site manufacture of a new polymer composite plastic liner within the damaged pipe. The CIPP process can release materials resulting in occupational and public health concerns. To understand hazards associated with CIPP-related emission exposures, an in vitro toxicity assessment was performed utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…These nonstyrene components of the emission mixture have shown to be responsible for toxicological effects ( S9 ). 51 PID sensors should not be used to estimate air pollution magnitude, gas-phase styrene concentrations, and the capabilities of these sensing technologies, and their limitations require scrutiny ( S9 ). 52…”
Section: Resultsmentioning
confidence: 99%
“…These nonstyrene components of the emission mixture have shown to be responsible for toxicological effects ( S9 ). 51 PID sensors should not be used to estimate air pollution magnitude, gas-phase styrene concentrations, and the capabilities of these sensing technologies, and their limitations require scrutiny ( S9 ). 52…”
Section: Resultsmentioning
confidence: 99%
“…Recent research on CIPP emissions have determined that styrene, benzaldehyde, phenol, and many other substances are often present in the air during the curing process [Teimouri Sendesi et al 2017]. Samples of these emissions have been shown to be harmful to lung cells, potentially predisposing exposed workers to the development or worsening of conditions such as fibrosis, obstructive pulmonary disease, and cancer [Kobos et al 2019].…”
Section: B-21mentioning
confidence: 99%
“… 2019: In the U.S., an inhalation toxicology study of materials emitted from four steam CIPP manufacturing sites indicated potential health risks as well as variations between worksites regarding emissions and toxicity. The evaluation identified biological pathways that require future evaluation and also demonstrated that exposure assessment of CIPP worksites should examine multiple chemical components beyond styrene, as many cellular responses were styrene-independent (Kobos et al 2019).…”
Section: Select Safety Related Eventsmentioning
confidence: 99%